Politics of violence : militancy, international politics, killing in the name - Heath-Kelly, Charlotte (Interventions, 2013)
"Politics of Violence uses ex-militant testimonies from Cyprus and Italy to explore the ways in which political violence is political, the functionality of violence, and the post-conflict consolidation of political authority"-